Factors Influencing the Decision to Purchase Soto Ayam Cak Dul in Surabaya - Wiwik Prihartanti; Ahmad Gamal; Pinky Pininta Dewi; Siti Lailatus Sofiyah; Mufthowif M; Wahyu Eko Cahyono; Agus Rahmanto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Product price and quality influence a person’s decision-making process. Price is a key factor in a person’s decision to make a purchase. The lower the price, the more interested the buyer will be; conversely, the higher the price, the less interested the buyer will be. Another factor that influences purchasing decisions is product quality. Product quality is crucial for buyers when making their choice. Consumers are more likely to purchase high-quality products even if the price is slightly higher. These two factors help determine the buyer’s choice when deciding on a purchase. Other factors, such as location and service quality, also influence purchasing decisions. This study aims to analyse the influence of price and product quality on purchasing decisions for Soto Ayam Cak Dul in Surabaya. The population in this study consists of customers who purchase Soto Ayam Cak Dul in Surabaya. The sample size for this study is 86 people. Data analysis was conducted using multiple linear regression with the aid of SPSS software version 26. The results of the study can be summarised as follows: price has a significant influence on the decision to purchase Soto Ayam Cak Dul in Surabaya. Product quality has a significant influence on the decision to purchase Soto Ayam Cak Dul in Surabaya. Price and product quality simultaneously have a significant influence on the decision to purchase Soto Ayam Cak Dul in Surabaya.